Prediction of long-term effects of juvenile idiopathic arthritis - Ye.M. Zaytseva (Zaslavsky O.Yu., 2017)
Background. Juvenile idiopathic arthritis (JIA) is characterized by chronic inflammation of the joints with progressive course and a strong tendency to development of early disability. Long-term follow up of a patients with JIA allows us to trace the evolution of the disease, and to assess the correlation between the course of pathological process and the type of disease onset, age, sex, degree of activity and other factors, which contribute to the use of more exact methods for early detection of the adverse health consequences of JIA and the correct treatment. The purpose of the research was an improvement of the prognostic criteria for JIA by the retrospective chart review in patients with disease duration 1 year and 5-7-10 years. Materials and methods. The study included 47 children with joints form of JIA aged from 2 to 18 years. For diagnosis, clinical examination, standard laboratory and instrumental tests were used. A regression analysis was used for the determination of prognostic criteria, the informative value of the features and the predictive factors for each of criteria. Results. It was established that for prediction of the further 5-7-year course of JIA, the patient's gender, inflammation of small joints of the hands, the presence of the rheumatoid factor (RF) played an essential role; and for 10-year and longer prognosis - the presence of eye lesions, the number of both affected and active joints were important. The significance of the following parameters has increased in prognostic model: the presence of RF, the duration of morning stiffness, radiological stage of the disease, laboratory indicators, such as erythrocyte sedimentation rate, level of C-reactive protein. For the 10-year prognosis of JIA, the effectiveness of treatment with methotrexate on initial stage was beneficial. These models determine variants of long-term course of JIA and include remission (up to 2 points), stabilization of the pathological process (from 2 to 3 points), which are assessed as favorable signs; and repeated exacerbations of the pathological process without progression of destructive changes in joints (from 3 to 4 points), clinical progression of disease, including radiological changes and joint destruction (more than 4 points), is classified as an unfavorable. Conclusions. The given methods for predicting the course of the JIA should be used at the initial stages of disease, it will allow to determine the real risk of adverse effects at early stage of pathological process and make it possible to choose adequate treatment.